Insights into the Molecular Architecture of a Peptide Nanotube Using FTIR and Solid‐State NMR Spectroscopic Measurements on an Aligned Sample1. Issue 40 (16th August 2013) - Middleton, David A.; Madine, Jillian; Castelletto, Valeria; Hamley, Ian W.
<x xml:space="preserve">Abstract</x> Queuing up: Molecular orientation within macroscopically aligned nanotubes of the peptide AAAAAAK can be studied by solid‐state NMR and IR spectroscopy. Line shape analysis of the NMR spectra indicates that the peptide NH bonds are tilted 65–70° relative to the nanotube long axis. Re‐evaluation of earlier X‐ray fiber diffraction data suggests that the peptide molecules are hydrogen‐bonded in a helical arrangement along the nanotube axis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>